Effect of Motivation on Employee Performance: A Case Study of Government Agency - Kanenge, Abel; Mwanza, Bupe (Management Journal for Advanced Research, 2023)
The overarching focus of this study was to establish the effect of motivation on employee performance at a Government Agency responsible for the collection, enforcement and administration of various taxes in Zambia. The study objectives were to establish the types of motivation the company provided to its employees, examine the employees’ expectations of motivation and assess the effect of motivation on employee performance. A quantitative approach to which a descriptive case study was adopted for this study. Stratified random sampling of participants was employed to select respondents from Lusaka Headquarters and a questionnaire with Likert scale statements was used for data collection. Questionnaires were administered via email and 183 respondents returned fully answered questionnaires. The findings revealed that 65% of motivation were motivated. The study also revealed that employees had expectations on the type of motivation to be provided to them by their management. Regarding the effect of motivation on employee performance, it was revealed that motivation influenced individual hard work, reinforcement of morals and integrity, rejection of under hand bribes by clients and many other effects. The findings of the hypothesis showed that the mean values were skewed towards the Likert responses ‘agree’ with 80% of employees agreeing to motivation variables. This confirmed that motivation affected employee performance by 100%. The study concluded that, motivation played a pivotal role where productivity through human effort was concerned. The study made three recommendations: The management and Board should understand human nature and their employees’ needs at workplace as this determined the direction on the correct motivation to provide to them. The Government Agency should create a committee of incentives provision comprising ordinary employees and management personnel in order to have inclusive suggestions of incentives that have a bearing on the needs of the employees. Lastly employees should be informed and oriented on the role of motivation as it influences their daily work efforts.